Diagnostic and Therapeutic Management of the Thoracic Outlet Syndrome. Review of the Literature and Report of an Italian Experience - Camporese, Giuseppe; Bernardi, Enrico; Venturin, Andrea; Pellizzaro, Alice; Schiavon, Alessandra; Caneva, Francesca; Strullato, Alessandro; Toninato, Daniele; Forcato, Beatrice; Zuin, Andrea; Squizzato, Francesco; Piazza, Michele; et al. (Frontiers in Cardiovascular Medicine, 2022)
The Thoracic Outlet Syndrome is a clinical potentially disabling condition characterized by a group of upper extremity signs and symptoms due to the compression of the neurovascular bundle passing through the thoracic outlet region. Because of the non-specific nature of signs and symptoms, to the lack of a consensus for the objective diagnosis, and to the wide range of etiologies, the actual figure is still a matter of debate among experts. We aimed to summarize the current evidence about the pathophysiology, the diagnosis and the treatment of the thoracic outlet syndrome, and to report a retrospective analysis on 324 patients followed for 5 years at the Padua University Hospital and at the Naples Fatebenefratelli Hospital in Italy, to verify the effectiveness of a specific rehabilitation program for the syndrome and to evaluate if physical therapy could relieve symptoms in these patients.